1986
DOI: 10.1103/physrevb.34.7670
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation and recombination in spin-polarized atomic hydrogen

Abstract: %e have studied relaxation and recombination processes in compressed, doubly polarized atomic hydrogen at temperatures from 0.13 to 0.60 K and magnetic fields from 3 to 9 T. The gas and surface dipole three-body recombination rate constants at a field of 7.6 T are measured to be, respectively, L~=8.9(8))&10 ' cm s ' and 1. , =1.2{4})(10 cm s '. They decrease slowly with field and I. , exhibits no significant angular dependence. The three-body recombination rate due to hyperfine mixing has also been measured. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 46 publications
2
12
1
Order By: Relevance
“…This is the first directly measured value based on independent determinations of the recombination rate and surface density. It agrees well with the calculations of de Goey et al [15], but is an order of magnitude lower than the L 3b values reported in several previous works [9,10,11]. In all previous measurements of surface recombination σ was inferred into the rate equations through the adsorption isotherm.…”
supporting
confidence: 91%
“…This is the first directly measured value based on independent determinations of the recombination rate and surface density. It agrees well with the calculations of de Goey et al [15], but is an order of magnitude lower than the L 3b values reported in several previous works [9,10,11]. In all previous measurements of surface recombination σ was inferred into the rate equations through the adsorption isotherm.…”
supporting
confidence: 91%
“…3 obtained here at T 2 202͑2͒ mK and s b 5.9͑4͒ 3 10 13 cm 22 . At low densities, K bbb remains constant, K bbb 8.4͑3.5͒ 3 10 225 cm 4 s 21 , which agrees with the above fitting result and data given elsewhere [16]. However, starting at s b l 2 2 ഠ 3, K bbb decreases steadily and at the highest degeneracy it is suppressed by a factor of 11 (2).…”
supporting
confidence: 90%
“…In fact, some experimental studies of TBA do exist, but they have been carried out under conditions not relevant to primordial chemistry. Measurements have been carried out for spin-polarized atomic hydrogen, but at temperatures of 130 − 600 mK and magnetic fields of 3 − 9 T [13]. TBA measurements have also been performed with ultracold atoms at ∼ 10 − 500 nK, though not yet with atomic H [14].…”
Section: Three Body Associationmentioning
confidence: 99%